Uterine rupture mimicking Wunderlich’s syndrome in pregnancy: An unfortunate case - Kheng, Hooi Chan; Harivinthan Sellappan; Firdaus Hayati; Azlanudin Azman (Warminsko-Mazurska Izba Lekarska w Olsztynie, 2022)
Introduction: Wunderlich’s syndrome (WS), characterized by non-traumatic renal haemorrhage into the subscapular and perinephric space is a rare entity in pregnancy. Aim: This article highlights the incidental discovery of a pregnant woman with WS that resulted in emergency nephrectomy. Case study: A 31-year-old gravida 4 para 3 female with 3 previous caesarean sections presented with acute abdomen and was in shock. The abdominal ultrasound revealed gross haemoperitoneum. With the preoperative diagnosis of a uterine rupture, surgical exploration was done showing an extensive right perinephric hematoma and active bleeding from the renal hilum. No renal tumor or pseudoaneurysm of the renal hilum was noted. Emergency nephrectomy was performed. Unfortunately, the foetus did not survive the ordeal. Results and discussion: WS occurs as a result of renal neoplasms, idiopathic causes, vascular diseases, infection, and miscellaneous. Ultrasonography can help to identify the perinephric hematoma, meanwhile, colour and/or spectral Doppler can aid in the detection of vascular pathologies. Contrast-enhanced computed tomography is still the imaging modality of choice. In pregnancy, a magnetic resonance imaging would be a better modality, avoiding radiation exposure to the foetus and consequent foetal malformations. Treatment includes arterial embolization and/or operative management such as nephrectomy. Conclusions: WS in pregnancy is a rare clinical entity requiring a high index of clinical suspicion for diagnosis. WS needs to be considered in pregnant patients presenting with shock with the presence of perinephric hematoma. A multidisciplinary approach is essential in providing optimum care.